2012
DOI: 10.5152/akd.2012.096
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of subclinical left ventricular systolic dysfunction in patients with obstructive sleep apnea by automated function imaging method; an observational study

Abstract: Objective: We aimed to evaluate the subclinical left ventricular (LV) systolic dysfunction with the automated function imaging method (AFI) based on speckle tracking echocardiography (STE) in obstructive sleep apnea patients (OSA) with normal left ventricular ejection fraction (LVEF) and without any confounding disease that can cause myocardial dysfunction. Methods: Twenty-one healthy individuals and 58 OSA patients were included in this observational cross-sectional study. According to the severity of disease… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
29
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(32 citation statements)
references
References 35 publications
2
29
1
Order By: Relevance
“…1,18,19 Altekin et al 20 have also shown on a smaller group of subjects with OSA, using speckle-tracking echocardiography, that longitudinal and circumferential systolic LV dysfunction is detectable in addition to the diastolic dysfunction. In contrast to similar previous studies 19,21,22 evaluating the subclinical cardiac damage in subjects with OSA, our study is the first study to assess the 3-layer longitudinal and circumferential functions of the myocardium in subjects with OSA.…”
Section: Discussionmentioning
confidence: 84%
See 1 more Smart Citation
“…1,18,19 Altekin et al 20 have also shown on a smaller group of subjects with OSA, using speckle-tracking echocardiography, that longitudinal and circumferential systolic LV dysfunction is detectable in addition to the diastolic dysfunction. In contrast to similar previous studies 19,21,22 evaluating the subclinical cardiac damage in subjects with OSA, our study is the first study to assess the 3-layer longitudinal and circumferential functions of the myocardium in subjects with OSA.…”
Section: Discussionmentioning
confidence: 84%
“…In most cases, LV systolic and diastolic dysfunction induced by OSA are temporary and functional, which could result in recovery when the hypoxia is improved or treated with CPAP therapy. 19 There are only a few published studies 19,21,22 that have used speckle-tracking echocardiography in the assessment of longitudinal and circumferential systolic myocardial functions in OSA subjects. In this study, we found that both longitudinal and circumferential strain in 3 myocardial layers were homogeneously decreased and correlated with the degree of OSA.…”
Section: Discussionmentioning
confidence: 99%
“…Infl ammation plays an important role in the pathogenesis of atherosclerosis (20). Hypoxia and systemic infl ammation may lead to progressive atherosclerosis and contribute to increased risk of CVD in patients with OSA (21)(22)(23). Increased levels of infl ammatory markers are associated with increased cardiovascular risk (24).…”
Section: Discussionmentioning
confidence: 99%
“…It has been shown in numerous studies that strain measurements by speckle tracking echocardiography is useful in subclinical detection of cardiac involvement in many systemic diseases (22,24,25). Recently, Baggish et al (6) demonstrated, in a longitudinal study, that a 90 day period of endurance exercise training increased the LV strain without changing the LV-EF.…”
Section: Left Ventricular Systolic Functions and Left Ventricular Strainmentioning
confidence: 99%